Antifungal Activity of Butterfly Pea Flower (Clitoria Ternatea L.) against Candida Albicans Causes of Dandruff - Ramdhini, Rizki Nisfi; Ramdini, Dwi Aula; Kamila, Dinda Shava (PSPP JOURNALS, 2024)
Dandruff is a common scalp problem characterized by flaking, itching, and redness. One of the causes of dandruff is the fungus Candida albicans. Under certain conditions, such as excessive oil production, this fungus can grow and become pathogenic. Butterfly pea flower is a plant known to contain antifungal compounds, including tannins, flavonoids, saponins, and alkaloids. This study aims to determine the antifungal activity of ethanol extract from butterfly pea flower against Candida albicans using SDA (Sabouraud Dextrose Agar) medium with the disk diffusion method. The concentrations of butterfly pea extract used were 5%, 15%, 30%, 60%, and 90%. The positive control used was ketoconazole, while the negative control was 1% CMC-Na. The results of the study indicate that the butterfly pea extract exhibits antifungal activity, as evidenced by the formation of an inhibition zone at a concentration of 90%, with an average inhibition zone of 3.7 mm. The positive control showed an inhibition zone of 14.38 mm, categorized as strong. In contrast, the negative control did not show any inhibition zone due to the lack of antifungal activity. Based on these results, it can be concluded that butterfly pea (Clitoria ternatea L.) has the potential for weak antifungal activity against Candida albicans.